Mmd Praktik Pengkajian Keluarga Dusun Jetis RW 06 Kecamatan Ungaran Timur Kabupaten Semarang Provinsi Jawa Tengah - Clara Laura; Noviyani, Feni; Hartini; Kusuma Intan Setianing Fifit; Nurul Amalia Hidayantika; Nurul Fadilah; Prisma Linda; Ari Widyaningsih (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Family Assessment Practice (FAP) is one of the student activities that must be carried out which is a form of real work in providing Community Midwifery Care Services. The aim of Family Assessment Practice (FAP) is that students are expected to be able to identify, plan, prioritize, implement and evaluate the management of community midwifery services using community movement and empowerment techniques as well as educational approaches for individuals, families, special groups or certain communities in achieving the SDGs. Benefits: Being able to get to know the culture and customs of the people in the work area of Leyangan RW 06 Hamlet on a daily basis. In implementing this community midwifery practice, the assessment is carried out by means of direct interviews and secondary data collection. Based on the study data, there were 49 toddlers who attended routine posyandu for TB/BB measurements. Of the 49 toddlers, 6 (12.2%) toddlers experienced stunting. Counseling is very important, but what is even more important is the level of attendance of the community itself, therefore when providing counseling it is necessary to pay close attention to their activities or type of work to ensure the level of attendance. . With the implementation results obtained, there were 6 toddlers covered by posyandu Rw. 06 experienced stunting. From the results of the study of 16 mothers of toddlers at posyandu with post-test results of 75%, they were aware of stunting. This suggests and requires refreshing of cadres on the proper and correct use of anthropometric equipment. It is hoped that with this there will be cooperation with community health centers. It is hoped that Leyangan Village, especially Rw. 06 can increase awareness of parents/caregivers in participating in posyandu for toddlers, and it is hoped that cadres and midwives will be more active in providing health information to the community, especially parents/caregivers   Abstrak Praktik Pengkajan Keluarga (PPK) merupakan salah satu kegiatan mahasiswa yang harus dilaksanakan dimana suatu bentuk kerja nyata dalam memberikan Pelayanan Asuhan Kebidanan Komunitas. Tujuan Praktik Pengkajan Keluarga (PPK) diharapkan mahasiswa mampu mengidentifikasi, merencanakan, memprioritaskan, mengimplementasikan, dan mengevaluasi manajement pelayanan kebidanan komunitas dengan teknik pergerakan dan pemberdayaan masyarakat serta pendekatan edukasi pada individu, keluarga, kelompok khusus ataupun pada komunitas tertentu dalam mencapai SDG’s. Manfaat Mampu mengenal budaya, dan adat kebiasaan masyarakat, diwilayah  kerja Dusun Leyangan RW 06 sehari-hari. Dalam pelaksanaan praktik kebidanan komunitas ini pengkajian  dilakukan dengan cara wawancara langsung, dan pengambilan data sekunder. Berdasarkan data pengkajian terdapat 49 balita yang mengikuti posyandu rutin untuk pengukuran TB/BB. Dari 49 balita terdapat 6 (12,2%) balita mengalami stunting. Penyuluhan sangat penting, tetapi lebih penting lagi adalah tingkat kehadiran masyarakat itu sendiri, karenanya ketika akan memberikan penyuluhan perlu diperhatikan dengan seksama aktifitas atau jenis pekerjaan mereka agar terjamin tingkat kehadirannya. . Dengan hasil implementasi yang didapatkan terdapat hasil 6 balita cakupan posyandu Rw. 06 mengalami stunting  Dari hasil pengkajian 16 ibu balita pada posyandu dengan hasil prites postes 75% Telah mengetahu Stunting. Hal ini menyarankan dan perlu adanya refreshing kader pada penggunaan alat antopometri yg baik dan benar diharap dengan ini ada kerja sama dengan puskesmas. Diharapkan Desa Leyangan khususnya Rw. 06 dapat meningkatkan kesadaran orang tua/ pengasuh  dalam ikut serta posyandu balita, serta diharapkan Kader dan Bidan lebih aktif memberikan informasi kesehatan kepada masyarakat khususnya orangtua/pengasuh.